2010
DOI: 10.4049/jimmunol.0902217
|View full text |Cite
|
Sign up to set email alerts
|

Altered Effector CD4+ T Cell Function in IL-21R−/− CD4+ T Cell-Mediated Graft-Versus-Host Disease

Abstract: We previously showed that transplantation with IL-21R gene-deficient splenocytes resulted in less severe graft-versus-host disease (GVHD) than was observed with wild type splenocytes. In this study, we sought to find mechanism(s) explaining this observation. Recipients of donor CD4+ T cells lacking IL-21R exhibited diminished GVHD symptoms, with reduced inflammatory cell infiltration into the liver and intestine, leading to prolonged survival. After transplantation, CD4+ T cell numbers in the spleen were reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
(42 reference statements)
3
19
0
Order By: Relevance
“…Blocking IL-21 significantly ameliorates pathology in the small intestine and colon in multiple murine models. 22,23,26 However, although IL-21-secreting cells are present in the small intestine and colon of animals in the xenogeneic GVHD model, the pathology observed in animals electively killed on day 10 or 20 was not severe enough to assess the actions of anti-IL-21 (not shown). Blocking IL-21 also decreases liver pathology in some, 23,26 but not all, 22,23 murine GVHD models, and had some beneficial effects in the xenogeneic model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Blocking IL-21 significantly ameliorates pathology in the small intestine and colon in multiple murine models. 22,23,26 However, although IL-21-secreting cells are present in the small intestine and colon of animals in the xenogeneic GVHD model, the pathology observed in animals electively killed on day 10 or 20 was not severe enough to assess the actions of anti-IL-21 (not shown). Blocking IL-21 also decreases liver pathology in some, 23,26 but not all, 22,23 murine GVHD models, and had some beneficial effects in the xenogeneic model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports by us and others show that inhibiting IL-21 also decreases disease severity in murine models of GVHD. [22][23][24][25][26] Specifically, disruption of IL-21 signaling, either genetically or via neutralizing mAbs, reduces transplant-related weight loss, tissue pathology, and mortality. Disease amelioration correlated with decreased numbers of CD4 ϩ T cells secreting IFN-␥ and a concomitant increase in the proportion of CD4 ϩ T cells expressing Foxp3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lu et al found that phosphorylation of STAT3, a transcriptional factor involved in Th17 cell differentiation 15 Transplantation with IL-21R-/-donor T cells resulted in less severe aGVHD, while sparing the GVL effect [71][72][73][74] . Furthermore, IL-21 blockade using a monoclonal antibody also decreased aGVHD 75 .…”
Section: Studies In Mouse Models Of Agvhdmentioning
confidence: 99%